2011
DOI: 10.1292/jvms.10-0336
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cutaneous Fibropapillomatosis with No Evidence of Papillomavirus Infection in a Piglet

Abstract: ABSTRACT. Multiple yellowish-white, cauliflower-like mass lesions on the skin of the head and back in a 4-month-old piglet were pathologically examined. These lesions had developed before the weaning period. Histologically, the cutaneous neoplasms were characterized by papillary outgrowth of connective tissue covered by thick epidermis. Hyperplasia of the epidermis was corresponded with proliferation of capillaries, lympho-plasmacytic infiltration, and proliferation of fibroblasts in the dermal stroma. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
(14 reference statements)
1
14
0
2
Order By: Relevance
“…However, the combination of epithelium and fibrous tissue as seen in the present case, has not been described in human nevi. Therefore, the authors prefer the term congenital fibropapilloma in this case, which previously has only been described in piglets (Vitovec et al, 1999;Nishiyama et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination of epithelium and fibrous tissue as seen in the present case, has not been described in human nevi. Therefore, the authors prefer the term congenital fibropapilloma in this case, which previously has only been described in piglets (Vitovec et al, 1999;Nishiyama et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital cutaneous (fibro)papillomas have occasionally been described in cattle (Desrochers et al, 1994) and pigs (Vitovec et al, 1999;Misdorp, 2003a;Nishiyama et al, 2011), and have only rarely been reported in horses (Garma-Aviña et al, 1981;White et al, 2004;Ruppin et al, 2013). Most of these cases are single verrucous or cauliflower-like lesions that occur on the head (Garma-Aviña et al, 1981;Misdorp, 2003b;White et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fibropapillomatosis associated with a herpesvirus is commonly found in various reptiles such as snakes, lizards, freshwater turtles, and tortoises from desert environments, in which all turtle species are considered more susceptible to severe infection (Wellehan & Johnson 2005, Schumacher 2006. The presence of fibropapilloma may not be necessarily linked to herpesvirus but also to other types of viruses such as those found in pigs, horses, cows, humans, and other mammals (Nishiyama et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Em um dos casos lesões proliferativas idênticas na pele do corpo, interpretadas como papilomatose, foram observadas num macho reprodutor adulto jovem e em outros três animais da mesma propriedade. Geralmente casos semelhantes de papilomatose cutânea são congênitos e podem ou não estar associados com papilomavírus (Nishiyama et al 2011). Não foram realizados testes específicos para detecção de antígeno viral.…”
Section: Papilomaunclassified